The generational happiness switch in Norway: the puzzle of miserable youth and happy seniors - Witoszek, Nina; Larsen, Mads (Frontiers in Psychology, 2026)
An alarming rise in youth ill-being is sweeping across many parts of the world. In Norway, surveys conducted since 1985 consistently identified young people as the happiest age group, while seniors ranked lowest in terms of well-being. Since the early 2010s, however, this pattern has reversed: happiness among seniors has increased, whereas the well-being of young people has declined sharply. Quantitative research attributes this shift to strained social relationships, mental health challenges, and growing anxiety about the future. Social media appears to exacerbate these difficulties, though its interaction with broader cultural and societal transformations remains poorly understood. This study combines qualitative interviews with Norwegian high school students, retirees, teachers, health professionals, and other youth experts (n = 48), alongside an analysis of public debates concerning the causes and manifestations of adolescent distress. We explore four central questions: Is Norway—one of the world’s wealthiest nations—living proof that “money cannot buy happiness”? What are the main causes of youth ill-being? How do young and old Norwegians interpret the new, digitally driven reality? And what explains seniors’ unexpected resilience and well-being amid climate anxiety, geopolitical instability, and economic uncertainty? Our findings suggest that the rise in youth unhappiness—while partly associated with social media use—must be understood within a broader cultural framework: as a symptom of weakening communal bonds and a deepening crisis of the cooperative, prosocial ethos that has long sustained Norwegian society. An open question remains as to the extent to which this young, increasingly competitive and self-centred generation may challenge that ethos and, in a long run, undermine the very foundations of Norwegian social democracy.